2019
DOI: 10.1111/1749-4877.12395
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between rodents and weeds in a lowland rice agro‐ecosystem: the need for an integrated approach to management

Abstract: Rodents and weeds are important pests to rice crops in Southeast Asia. The interaction between these 2 major pests is poorly documented. In temperate cereal systems, seeds of grass weeds can be an important food source for rodents and weed cover along crop margins provides important refuge for rodents. In 2012 and 2013, a replicated study (n = 4) in Bago, Myanmar compared 4 treatments (rodents and weeds; no rodents and weeds; rodents and no weeds; no rodents and no weeds) each of 0.25 ha in transplanted rice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Given that the landscape of fear seems to be what influences habitat use whilst rice is in its growing stages (Jones et al 2017), refuge habitats for rats such as dense vegetation near rice fields should be cleared and sanitation around the rice field maintained regularly to minimize rodent activity in the rice field. Regular weeding of fields reduces cover and alternate food source for rodents (Drost and Moody 1982;Htwe et al 2019;Puan et al 2011). The timing of control, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the landscape of fear seems to be what influences habitat use whilst rice is in its growing stages (Jones et al 2017), refuge habitats for rats such as dense vegetation near rice fields should be cleared and sanitation around the rice field maintained regularly to minimize rodent activity in the rice field. Regular weeding of fields reduces cover and alternate food source for rodents (Drost and Moody 1982;Htwe et al 2019;Puan et al 2011). The timing of control, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of control, i.e. prior to the onset of breeding, is also critical (Brown et al 2011;Htwe et al 2019;Stuart et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The study reported additive negative effects of rodent and weeds on crop yield, with the combined effect highest in the dry season. A clear recommendation from these findings is the need for concurrent weed and rodent management, especially during the early crop stages of rice production 28 . Such an interaction between weeds and rodents may not be unexpected but prior to this study, quantitative data were lacking.…”
Section: Rice and Rodents – An Important Food Security Issue In Asiamentioning
confidence: 89%
“…Intensification of annual cropping by transitioning from one crop of rice to two crops, two crops to three crops, or two crops of rice followed by a non‐rice crop ( e.g ., maize or pulses), are all likely to increase the impacts of rodent populations on crop yields given the ability of the major rodent pest species in Asia to increase their annual breeding output when high quality food is available for more of the year. This includes Rattus argentiventer (most SE Asian countries), 19–22 Rattus tanezumi (Philippines) 23–27 and Bandicota bengalensis (Myanmar and South Asia) 28–32 …”
Section: Rice and Rodents – An Important Food Security Issue In Asiamentioning
confidence: 99%
See 1 more Smart Citation